2007
DOI: 10.1590/s1413-35552007000200009
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre dois testes clínicos para avaliar a flexibilidade dos músculos posteriores da coxa

Abstract: Objective: To compare the results from fingertip-to-floor and straight leg raise tests by means of photogrammetry, investigate the concordance of hip angle findings between the two tests and evaluate the intra and inter-examiner reliability of the photogrammetric analysis procedure. Method: The tests were applied to 35 healthy male subjects (mean age 23 ± 3.4 years, height 170 ± 4 cm and weight 68 ± 11 kg). The subjects were divided into two groups on the basis of the test classifications. Surface markers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 22 publications
1
25
0
14
Order By: Relevance
“…Therefore, these findings can possibly be attributed to the identification of anatomical reference points, as the error of a few millimeters in their identification could compromise the obtained angular values 14 . These difficulties were minimized with photogrammetry, because during registration passive markers were fixed for further image analysis, which benefited the alignment of the segments 26 . It should be noted that, despite these minor changes, intrarater reliability in this study was classified as very strong for both instruments, regardless of group or assessment, a fact that reinforces the findings of Brosseauet al 27 , who had found more reliable results for knee ROM (ICC = 0.97) when performed by the same examiner.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these findings can possibly be attributed to the identification of anatomical reference points, as the error of a few millimeters in their identification could compromise the obtained angular values 14 . These difficulties were minimized with photogrammetry, because during registration passive markers were fixed for further image analysis, which benefited the alignment of the segments 26 . It should be noted that, despite these minor changes, intrarater reliability in this study was classified as very strong for both instruments, regardless of group or assessment, a fact that reinforces the findings of Brosseauet al 27 , who had found more reliable results for knee ROM (ICC = 0.97) when performed by the same examiner.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, true patients may have pain, reduced ROM, and other limitations that might intervene in the measurements. Harrison 23 , however, found that the method can also be used in patients with pain.…”
Section: Discussionmentioning
confidence: 99%
“…A flexibilidade muscular é definida como a habilidade de um músculo alongar-se, permitindo que a articulação se movimente através de toda a amplitude de movimento (ADM), irrestrita e sem dor. A perda da flexibilidade e consequente redução da ADM ocorre, entre diversas condições, pela diminuição da capacidade de um músculo deformar-se, relacionada à perda de força muscular e à presença de encurtamentos [1][2][3][4][5] . A redução da flexibilidade, principalmente em isquiotibiais, pode gerar desequilíbrio postural, déficit da ADM do joelho, do quadril e da coluna lombar e dificuldade em realizar movimentos amplos 3,5 .…”
Section: Introductionunclassified
“…A perda da flexibilidade e consequente redução da ADM ocorre, entre diversas condições, pela diminuição da capacidade de um músculo deformar-se, relacionada à perda de força muscular e à presença de encurtamentos [1][2][3][4][5] . A redução da flexibilidade, principalmente em isquiotibiais, pode gerar desequilíbrio postural, déficit da ADM do joelho, do quadril e da coluna lombar e dificuldade em realizar movimentos amplos 3,5 . Essas alterações contribuem para lesões e disfunções musculoesqueléticas 2,6 .…”
Section: Introductionunclassified